EFFECT OF MENTORING TECHNIQUE IN REDUCING AGGRESSIVE BEHAVIOUR AMONG SECONDARY SCHOOL STUDENTS IN ENUGU STATE (Journal of Guidance and Counselling Studies, 2021)
Aggression on the part of students at the secondary school level is an anti-social behaviour that could result to violence and abuse of persons or property. It is considered to be the most common and widespread emotional manifestation of many students at all levels of education. This study therefore investigated the effect of mentoring technique in reduction of aggressive behaviour among secondary school students in Enugu North Local Government of Area. Three research questions and three null hypotheses guided the study. Quasi-experimental design was adopted for the study. A sample of 120 SS1 and JSS1 students was drawn from a total population of 468 students with aggressive behaviour. The instrument for data collection was Aggressive Behaviour Questionnaire. Statistical mean and Analysis of Co-Variance (ANCOVA) were used for data analysis. Results from the study showed that mentoring technique was significantly effective in reducing aggressive behaviour among secondary school students. The results also showed that mentoring technique was more effective in reducing aggressive behaviour among female and older secondary school students than their male and younger counterparts respectively. However, the finding of the study revealed that the difference in the effectiveness of mentoring technique in reducing aggressive behaviour among the students based on gender and age was not significant. It was recommended among others, that mentoring technique should be adopted by school guidance counsellors and other allied professionals as an effective treatment for helping students with aggressive behaviour to improve their life skills by becoming a better individual in the society and also living peacefully with their fellow students in the school environment and outside the school.